DIVERSIFIKASI OLAHAN JAGUNG SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH DI DESA WADIABERO - Muhamad noor azizu; Peliyarni; Wulan Riski Yanti (Jurnal Visi Pengabdian Kepada Masyarakat, 2023)
One of the abundant agricultural products in Wadiabero Village is corn. However, the utilization of corn agricultural products has not been maximized, and people tend to directly sell the corn to make ends meet. The objectives of this training are: 1. to provide solutions to partners on how to take advantage of the abundant sweet corn harvest in the Wadiabero Village area to be processed into nutritious and marketable food products using simple technology. 2. Increasing knowledge and skills as well as entrepreneurial opportunities for farmer mothers in processing diversified sweet corn processed products in the form of puddings and tray cakes, in order to increase family income. The result of the activity is an increase in community knowledge and skills in corn processing and the creation of processed products such as corn balls, kaagung mutara and corn hawaiian ice. It is hoped that this product will have the potential to become a household-scale small industrial business as a diversification of processed corn and provide motivation for the creation of the latest processed corn. Keywords: Wadiabero; processed; Businessman